(3GdJfVjO aj ENJUGQ GdJegjOs - (3CHh YHO Gddg eGdc Hf hgjHs; (3GHf YHO GdHQ , CHh YeQ jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj,J (B463 (3g` s
(3ChdgG (B:s
(3jHJOF HGdYed ai ZSd GdYjOjf hGdfOGA ajgeG hGdGbGeI s
(3BNQgG (B:s
(3jfJgi HHGH eG jLhR ddeMQe Gcdg ef GdUjO jJdhg ai GdKGdK HbjI eG jLhR ddeMQe Gcdg ef GdUjO s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
Keywords: (3GdMOjK h GdeUWdMs